PENGGUNAAN CAMPUR KODE PADA KOLOM KOMENTAR AKUN INSTAGRAM DEDDY CORBUZIER - Mia Salsabila; Siti Rukiyah; Yessi Fitriani (Literasi : Jurnal Bahasa dan Sastra Indonesia serta Pembelajarannya, 2022)
The problem in this study is code mixing in the comment column of Deddy Corbuzier’s instagram account. This study aims to identify and describe the forms of code mixing that occur in the comment column of instagram accounts. The method used in this research is descriptive qualitative method in studyng linguistic phenomena with a Sociolingustics approach. the data source of this research is the comment column contained in Deddy Corbuzier’s instagram account upload on February 22 – February 28, 2022. Data collection was carried out using the free-of-conversation (SBLC) listening technique, documentation technique,and note-taking technique. The validity of the data was obtained through data triangulation, method triangulation, and theoretical triangulation. The analytical technique used in this study was a data analysis technique using the Miles and Huberman model, namely thedata reduction stage of data presentation and drawing conclusions. The results of this study indicate that the code mixing contained in the column Deddy Corbuzier’s instagram account comment, namely in the form of words and phrases. Code mixing in the form of 215 words and 84 phrases. The factors causing code mixing include background, situation, attitude speaker and language.